2020
DOI: 10.1097/md.0000000000019950
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between body mass index, neck circumference, and waist-hip ratio as indicators of obesity among a cohort of adolescent in Bahrain

Abstract: Return the portable scales to the cabinet drawers. 2.5.4 Sitting Box  Remove the bungee cord from around the sitting box and store the strap in the anthropometry storage container.  Leave the sitting box against the corner wall where the mirrors are located.  Raise the seat located beside the sitting box. 2.5.5 Stadiometer  Replace the 9-volt battery in the digital measurement device for the stadiometer. NOTE: The facility and equipment specialist is expected to do this.  Calibrate the stadiometer using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…This could indicate that adolescent overweight or obesity has reached a plateau in recent years in the State of Kuwait. A comparison of our findings with those of the regional prevalence of overweight or obesity also showed similar results [ 24 28 ]. However, a recent study in Oman reported much lower overweight/obesity levels for Omani adolescent females (22.4%) and males (22.5%) [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…This could indicate that adolescent overweight or obesity has reached a plateau in recent years in the State of Kuwait. A comparison of our findings with those of the regional prevalence of overweight or obesity also showed similar results [ 24 28 ]. However, a recent study in Oman reported much lower overweight/obesity levels for Omani adolescent females (22.4%) and males (22.5%) [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…The activity of aromatase, resulting in an imbalance in the distribution of these sex hormones (testosterone and estradiol), is crucial in a variety of physiological processes [ 12 ]. Anthropometric parameters, like body mass index (BMI), neck circumference (NC), waist circumference, and waist-to-hip ratio (WHR), among others, have been linked with changes in sex hormone levels in both men and women across different age groups [ 13 , 14 ]. These measures of adiposity have been linked to increased levels of estrogen and decreased levels of testosterone in both men and women [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patil C et al 19 have found that in males, the correlation of neck circumference with BMI and waist circumferencewas weak (r=0.494) and moderate (r=0.556) correlation respectively whereas in fe-males the correlationof neck circumference was moderate with BMI (r=0.590) and waist circumference(r=0.614). Tantawy SA et al 20 in their study have concluded that weak, positive correlation between neck circumference and BMI. Alfadhli et al 21 in their Saudi Arabia study found positive associations between NC and WC (r=0.7 and r=0.5), BMI (r=0.5 and r=0.5) in males and females respectively.…”
Section: Discussionmentioning
confidence: 91%